Smart and sustainable cities: What is smart? What is sustainable? - Laconte, Pierre (Springer, 2018)
Smart cities are cities using information and modern communications technology to connect activities hitherto unconnected. This became a buzzword supported by a variety of interests including, among others, the producers of knowledge-based consulting services making use of big-data collections. Four examples of smart cities applications are presented. Sustainable cities are those that meet the needs of their present citizens without compromising the ability of future generations to meet their own needs, reconciling the environmental, social and economic pillars of long- term durability. Sustainability applies at the levels of individual buildings, neighborhoods, entire cities, their peripheries and their regions. Benchmarking aims at systematically comparing sustainability in space and time, at each of these geographic levels. Focus is put on assessment criteria reflecting political orientations. Three pioneering examples are presented.
Keywords: Urbanität; Vernetzung; Nachhaltigkeit; Energieversorgung; Energieverbrauch; Kreislaufwirtschaft; Bürgerbeteiligung